Avoiding the Ask: A Field Experiment on Altruism, Empathy, and Charitable Giving - Andreoni, James; Rao, Justin M.; Trachtman, Hannah (Journal of Political Economy, 2017)
If people enjoy giving, then why do they avoid fund-raisers? Partnering with the Salvation Army at Christmastime, we conducted a randomized field experiment placing bell ringers at one or both main entrances to a supermarket, making it easy or difficult to avoid the ask. Additionally, bell ringers either were silent or said “please give.” Making avoidance difficult increased both the rate of giving and donations. Paradoxically, the verbal ask dramatically increased giving but also led to dramatic avoidance. We argue that this illustrates sophisticated awareness of the empathy-altruism link: people avoid empathic stimulation to regulate their giving and guilt.